2009
DOI: 10.1073/pnas.0905010106
|View full text |Cite
|
Sign up to set email alerts
|

An essential role for RPE-derived soluble VEGF in the maintenance of the choriocapillaris

Abstract: Clinical and experimental observations indicate a role for VEGF secreted by the retinal pigment epithelium (RPE) in the maintenance of the choriocapillaris (CC). VEGF in mice is produced as three isoforms, VEGF120, VEGF164, and VEGF188, that differ in their ability to bind heparan sulfate proteoglycan. RPE normally produces the more soluble isoforms, VEGF120 and VEGF164, but virtually no VEGF188, reflecting the fact that molecules secreted by the RPE must diffuse across Bruch's membrane (BrM) to reach the chor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
335
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 460 publications
(364 citation statements)
references
References 37 publications
12
335
1
3
Order By: Relevance
“…Destruction of the RPE cells has been reported in animal models of disease responsible for secondary choriocapillaris atrophy (5,11) . A requirement for vascular endothelial growth factor, which is produced by RPE cells, has been demonstrated for choroidal maintenance; therefore, this growth factor may play a role in choroidal thinning (4,12) . The retinas, and especially the photoreceptor cells, are the most metabolically active tissues in the body, and their oxygen consumption is faster than that seen in other tissues (13) .…”
Section: Discussionmentioning
confidence: 99%
“…Destruction of the RPE cells has been reported in animal models of disease responsible for secondary choriocapillaris atrophy (5,11) . A requirement for vascular endothelial growth factor, which is produced by RPE cells, has been demonstrated for choroidal maintenance; therefore, this growth factor may play a role in choroidal thinning (4,12) . The retinas, and especially the photoreceptor cells, are the most metabolically active tissues in the body, and their oxygen consumption is faster than that seen in other tissues (13) .…”
Section: Discussionmentioning
confidence: 99%
“…VEGF has been found to be produced constitutively by RPE cells, 43 and was increased in response to MAC formation on primary RPE cells. 44 Sustained low level secretion of VEGF is believed to be necessary for the normal development and maintenance of the choriocapillaris, 45 whereas on the other hand, pathological increases in VEGF contribute to several ocular diseases including neovascularisation in wet AMD. 46 Given that RPE cell-cell contacts may become disrupted in AMD, our findings therefore potentially link complement activation and sub-lytic MAC formation to increased VEGF secretion, and the neovascular processes observed in late stage disease.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it was shown that PEDF can act as an antiangiogenic factor that inhibits endothelial cell proliferation in the choriocapillaris. VEGF is another vasoactive factor of RPE known as preventing endothelial cell apoptosis (Saint-Geniez et al, 2009). In a healthy eye, PEDF and VEGF are secreted at opposite sides of the RPE cell.…”
Section: Expression Of Growth Factors and Major Signaling Pathwaysmentioning
confidence: 99%